PENGEMBANGAN BAHAN AJAR BERBASIS MODEL KOMUNIKATIF UNTUK MENINGKATKAN KETERAMPILAN BERBICARA BAHASA ARAB - Amrini Shofiyani’; Rina Dian Rahmawati (Institut Pendidikan Tapanuli Selatan, 2020)
It became plausibly prominent to conduct a research which was focused on developing an instructional design for this subskill. This research aimed at constructing an instructional design for speaking skills which was considered suitable with the students’ characteristics and their needs as well. Developing an appropriate textbook is considered one way of solving the problems in teaching-learning process. Based on the preliminary research done in the field, it was shown that the materials of speaking skills used at Universitas K.H. A. Wahab Hasbullah were not systematically designed. In addition, the students’ characteristics and needs were not taken into account in selecting the materials. In other words, an appropriate instructional design for this course was not sufficiently available. Based on the above evaluations and revisions on the design, several significant points can be derived: (1) the design was systematically constructed based on Dick and Carey System Approach, (2) the design was considered appropriate to apply in class, (3) the design was suited to both the teachers’ and the students’ needs; this was reflected on the positive opinions expressed by the teachers and the students on the questionnaire as well as the result of the post test.